When Catalogers and Archivists Come Together: The Creation of the Metadata Justice in Oklahoma Libraries Archives Symposium - Beezley, Shay; Scheele-Clark, Heather (Collaborative librarianship, 2023)
The Metadata Justice in Oklahoma Libraries & Archives Symposium is an event focused on improving metadata and description for historically overlooked communities in library and archival collections. This event is a result of collaboration between people working in libraries and archives in an environment that has traditionally kept library and archives work separate. Two members of the 2023 Planning Team discuss the symposium's inception, event logistics, successes, opportunities for growth, and the impact that this symposium has on the Oklahoma library and archives community.